When Drniš Came to the Sea: Croatian Nationalism, Dalmatian Regionalism, and the Politics of Identity, 1990–2001 - Ashbrook John E. (Comparative Southeast European Studies)
This article analyzes the politicization of identities in Dalmatia during the turbulent decade of the 1990s. It argues that during the Croatian War of Independence (or the Homeland War), several factors led to the politicized delegitimization of Dalmatian identity outside a Croatian nationalist context. These included the proximity of the Serbian Krajina rebellion, the flood of displaced persons from the Croatian hinterland to the coastal cities, the attacks of the Croatian Democratic Union (HDZ)-led government on the regionalist Dalmatian Action party and regionalism in general. The author also analyzes how many coastal Croats reacted to and described their hinterland cousins, mirroring the rural/urban divide that characterized descriptions of Serbs by nationalist Croats during the dissolution of Yugoslavia.